Spinning your Wheels? Practical Time Management Solutions for Chairpersons - Craig D Hlavac (Academic Chairpersons Conference Proceedings, 2015)
Ever feel like you are spinning your wheels as chair? Poor time management may be to blame. In a recent study of department chairs/directors, 81% of respondents indicated the amount of time required to respond to communications was more than anticipated; 31% indicated time management was their single biggest challenge as chair (Schwinghammer et al., 2012). This session will provide participants with a brief overview of several recent publications relevant to time management for department chairpersons, followed by guided small-group discussions related to time management concerns. Practical recommendations and suggestions for improving efficiency and decreasing stress will be discussed.
Keywords: Time Management; Leadership; Prioritize; Delegate